Cognitive components of self-concepts of successful versus unsuccessful athletes - Lovyagina, A. E. (Theory and Practice of Physical Culture, 2018)
Objective of the study was to analyze the cognitive components of the self-concept and behavioural models of successful versus unsuccessful track and field athletes. Applied for the study purposes were the following methods: Self-concept measuring Twenty Statements Test (TST) by M. Kuhn and T. McPartland and Behavioural Models Questionnaire by K. Thomas. Subject to the study were track and field athletes (n=56 including 28 males and 28 females) qualified Class I to Honorary Master of Sports. The study showed domination of the expressive and instrumental traits and cooperation-focused behavioural type in the successful athletes` self-concepts; versus the dominant intentional traits and competitive behavioural models in the unsuccessful athletes` self-concepts. Competitive success in the modern track and field athletics is known to largely depend on the cognitive component of the self-concept and athlete`s behavioural model. This is the reason why athletes need to clearly understand their physical and personality qualities to facilitate behavioural and competitive progress.